Latest Evidence on Non-Communicable Disease Management (NCD) during COVID-19 Pandemic - Rahman, Abdul Rashid Abdul (International Journal of Human and Health Sciences (IJHHS), 2021)
The year 2020 has been dominated by a communicable disease which most did not see coming and are ill- prepared to handle. While daily headlines the world over are dominated by new cases and death from COVID-19, other major health issues must not take a back seat. As of 30thNovember this year, 357 people have died of COVID-19 in Malaysia,while close to 15,000 Malaysians died of Ischemic Heart Disease (IHD) alone. With IHD and cerebrovascular accident (CVA) being the number 1 and number 3 causes of death (15% and 8% of all death, respectively) our focus on COVID-19 must not distract us from the ‘elephant in the room’. Evidence from UK showed that while hospitalization due to acute myocardial infarction (AMI) has significantly decreased by 50%, out of hospital cardiac arrest has significantly increased by 56%; and in hospital mortality from AMI has increased by at least 35% during the pandemic. Patients are shying away from coming for scheduled follow ups, and there has been a reduction in guideline recommended care for NCD. This is confounded by early scare which suggested that treatment of risk factors for NCDs, especially for hypertension, dyslipidemia, and diabetes, may increase susceptibility to and worsen prognosis for patients with COVID-19. Since COVID-19 is a new entity, latest evidence generated are mainly from observational studies with few clinical trials with the exception of vaccine trials. What do we know about management of NCD in the COVID-era?Since the discovery that SARS-COV-2 virus attached itself to the ACE2 receptors before entering cells, alarm bells were sounded that patients treated with RAAS inhibitors may be susceptible to and have worse prognosis. Withup to 60% of hypertensiveworldwide taking this class of drugs, the concern is understandable. Reassuringly, 6 observational studies from 4 countries and 1 RCT from a 5th country showed this not to be true. Studies from China and Italy showed that those on RAAS inhibitors have better prognosis and this has triggered an RCT which hypothesized that pre-treatment with angiotensin receptor blockers may be beneficial in preventing pulmonary damage in these patients. Another RCT is looking at recombinant human ACE2 as treatment for patients with COVID-19. In diabetic patients, an observational study from New York showed those on statin has reduced mortality compared to non-user and in a large UK based primary care setting there was no increased risk of COVID-19 among patients prescribed SGLT2 inhibitors. The SGLT2 inhibitors have been proven to improve clinical outcome including mortality in diabetics and could be safely used to treat patients during the pandemic. Based on a nationwide retrospective cohort in the UK, overall mortality was higher for diabetics admitted to ICU or HDU and with greatest mortality impact in younger patients.The next few months will see more prospective intervention studies publishedaddressing the various unanswered questions. It is worth remembering that substandard care is responsible for upto 84% of CV death. Hence, we shouldnot let our guards down with NCDs even when the world’s attention is focused on COVID-19. International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S10